2022
DOI: 10.1007/s00467-022-05806-9
|View full text |Cite
|
Sign up to set email alerts
|

Humoral immune response and live-virus neutralization of the SARS-CoV-2 omicron (BA.1) variant after COVID-19 mRNA vaccination in children and young adults with chronic kidney disease

Abstract: Background Data on humoral immune response to standard COVID-19 vaccination are scarce in adolescent patients and lacking for children below 12 years of age with chronic kidney disease including kidney transplant recipients. Methods We therefore investigated in this retrospective two-center study (DRKS00024668; registered 23.03.2021) the humoral immune response to a standard two-dose mRNA vaccine regimen in 123 CKD patients aged 5–30 years. A live-virus as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 47 publications
(66 reference statements)
1
11
0
Order By: Relevance
“…The included studies characteristics are provided in Table 1 [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. All seven selected studies included 254 pediatric and adolescent KTRs, who were naïve to COVID-19 infection, based on prior to vaccination SARS-CoV-2 IgG titers or patient medical history, and who received two doses of the SARS-CoV-2 mRNA vaccine.…”
Section: Resultsmentioning
confidence: 99%
“…The included studies characteristics are provided in Table 1 [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. All seven selected studies included 254 pediatric and adolescent KTRs, who were naïve to COVID-19 infection, based on prior to vaccination SARS-CoV-2 IgG titers or patient medical history, and who received two doses of the SARS-CoV-2 mRNA vaccine.…”
Section: Resultsmentioning
confidence: 99%
“…While titer levels after the second vaccination in GN patients receiving CNI did reach same levels as in healthy controls, the humoral response in investigated KTx patients was markedly decreased, and the overall seroconversion rate was 56%. Previously, a humoral response was reported in 62% of Ktx patients [ 6 ]. A reduced capability of primary vaccination to elicit a humoral response was also seen in adult and adolescent patients after solid organ transplantation [ 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, primary, as well as booster vaccinations, are encouraged for immunosuppressed children [ 3 , 4 ]. However, as only limited data [ 5 , 6 ] on the immunological response to the vaccination exist in this age group, expert-based recommendations have displaced evidence-based recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, while the neutralizing activity against Delta and Omicron variants in transplant patients remained low after receiving the third vaccine dose, the Fc-mediated effector function in SOTRs reached a level similar to that of a cohort of healthy individuals ( 104 ). Stich also indicated that while the standard mRNA vaccine regimen could weaken the humoral immune response in immunocompromised children and adolescents with kidney disease, reducing the vaccine dose could result in effective antibodies against Omicron in approximately 10% of patients ( 110 ). In addition, the study revealed that patients who did not develop humoral immune responses after the third vaccine dose either received an immunosuppressive regimen that included MMF or had an inherited T-cell defect disease.…”
Section: Vaccination For Prevention Of Omicron Infection In Ktrsmentioning
confidence: 99%